Comparative Distribution of Inheritance Assets Against Adopted Children Based on the Compilation of Islamic Law and Civil Law - Aulia, Febriana Putri; Kusriyah, Sri; Suwondo, Denny (Jurnal Konstatering, 2025)
Abstract. This study aims to examine and analyze the legal status of adopted children regarding the distribution of inheritance assets in terms of the Compilation of Islamic Law and Civil Law, as well as to analyze the responsibilities of Notaries in making wills for adopted children. The approach method used in this study is a normative juridical approach. The specifications of this study use descriptive analysis. The type of data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection method uses literature studies. The data analysis method used in this study uses qualitative analysis methods. The research results show that the distribution of inheritance to adopted children differs. This provision can be seen from the perspective of the Compilation of Islamic Law, as regulated in Article 209 of the Compilation of Islamic Law, which states that "...The granting of inheritance to adopted children through a mandatory will is a maximum of ⅓ of the inheritance assets "based on the decision of the Religious Court, then the mandatory will deed is made by a Notary,while the distribution of inheritance to adopted children referring to Staatsblad 1917 Number 129 considers adopted children to be equal to biological children but according to the Civil Code the child cannot be an heir so that in the inheritance of adopted children can be given the inheritance of adoptive parents through a testament by considering Legitimie Partice. The main difference between these two perspectives is that in the Compilation of Islamic Law the granting of inheritance to adopted children is limited to no more than 1/3 of the portion through a mandatory will, while in Staatsblad 1917 Number 129 adopted children are given the same rights as biological children. However, both have similarities, namely they have the right to receive property from their biological parents but the granting is done in different ways.